Pengenalan Struktur Data dan Perannya dalam Pemrograman - Satriani Satriani; Dewi Andriany; Rusmawati Rusmawati; Mima Mima; Masnur Masnur; Salwana S; Ketrin Rinayanti Manullang (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Data structures are one of the most important foundations of computer science, defining how information is stored, organized, and manipulated within a computing system. Without a proper understanding of data structures, a software developer will struggle to design efficient, scalable, and reliable systems. This article aims to provide a comprehensive overview of the fundamental concepts of data structures and their crucial role in modern programming practice. It covers various types of data structures—from linear structures such as arrays, linked lists, stacks, and queues to non-linear structures such as trees, graphs, and hash tables—and discusses criteria for selecting an appropriate data structure based on the problem context. The method used is a systematic literature review of relevant scientific publications, technical reports, and official documentation from 2026 onward. The results of the study indicate that selecting an appropriate data structure directly affects the time and space complexity of an algorithm, which ultimately impacts the overall performance of a software system. Furthermore, this article also identifies several gaps in the literature related to the teaching of data structures in academic settings, particularly in Indonesia. It is hoped that this article will serve as a useful academic reference for students, researchers, and practitioners in the fields of information technology and software engineering.